Forced (Queer) migration and everyday violence: The geographies of life, death, and access in Cape Town. Issue 89 (February 2018) - Bhagat, Ali
Highlights: State-structured heteronormativity in Cape Town is examined through interview data with LGBT+ refugees. The debates of the Right to the City is theorized through Necropolitics and the politics of abandonment. Issues of access to the state are explored through Cape Town's myth as a safe haven for LGBT+ people. Survival with regard to employment, shelter, and everyday violence is illustrated through ethnographic data. Abstract: LGBT+ rights have recently gained international attention across the continent and have resulted in expanding tensions surrounding access to both city and state in South Africa. The experiences of LGBT+ asylum seekers, an underexamined group of migrants in South Africa, adds further complexity to the literature that has already challenged common-sense notions of Cape Town as a safe haven for sexual minorities. Increasing xenophobic tensions in South Africa's major urban centres combined with neoliberal-led cut-backs at municipal and national levels has further hidden and made invisible the struggles of LGBT+ asylum seekers. Accessing shelter and employment are interrelated facets of the right to the city as these aspects determine whether forcibly displaced queer people are allowed to live or are simply abandoned and left to die. Thus, this article asks, 'What is the interplay between access to the right to the city and the opposing social realities of death?' Using data from fieldwork conducted in 2014–2015 in Cape Town with NGOs and asylum seekers, I seek to examine the violent processes in which state-structured violence embedded in the heteronormative urban space impedes the survival of forcibly displaced queer people. I argue that LGBT+ asylum seekers in Cape Town navigate a landscape of abandonment and death in their attempts to access the right to the city.